What Moves Them? Active Transport among Inhabitants of Dutch Deprived Districts. (26th September 2013) - Saris, Carla; Kremers, Stef; Van Assema, Patricia; Hoefnagels, Cees; Droomers, Mariël; De Vries, Nanne
Abstract : Background . Active modes of transport like walking and cycling have been shown to be valuable contributions to daily physical activity. The current study investigates associations between personal and neighbourhood environmental characteristics and active transport among inhabitants of Dutch deprived districts. Method . Questionnaires about health, neighbourhoods, and physical activity behaviour were completed by 742 adults. Data was analysed by means of multivariate linear regression analyses. Results . Being younger, female, and migrant and having a normal weight were associated with more walking for active transport. Being younger, male, and native Dutch and having a normal weight were associated with more cycling for active transport. Neighbourhood characteristics were generally not correlated with active transport. Stratified analyses, based on significant person-environment interactions, showed that migrants and women walked more when cars did not exceed maximum speed in nearby streets and that younger people walked more when speed of traffic in nearby streets was perceived as low. Among migrants, more cycling was associated with the perceived attractiveness of the neighbourhood surroundings. Discussion and Conclusion . Results indicated that among inhabitants of Dutch deprived districts, personal characteristics were associated with active transport, whereas neighbourhood environmental characteristics were generally not associated with active transport. Nevertheless, interaction effects showed differences among subgroups that should be considered in intervention development.